Hiving off the non-essential: analysing which public organizations outsource administrative overhead. (June 2019) - Boon, Jan; Verhoest, Koen; De Borger, Bruno
This study contributes to our understanding of the characteristics of public organizations that are more likely to outsource administrative overhead. Despite the climate of ongoing crisis that urges public organizations to focus their resources on core tasks, little is known about the characteristics of organizations that hive off the delivery of non-essential administrative overhead processes to the private sector. This study runs a panel data Tobit model to test whether different effect sizes of structural, institutional and political characteristics are found regarding the probability of outsourcing and the degree of outsourcing of administrative overhead. We find that organizational size, formal autonomy, inertia and time matter for understanding the outsourcing of public organizations. Points for practitioners: Across the globe, governments have turned to a rationalization of administrative overhead in response to austerity demands posed by the global financial crisis. The present study shows that large differences exist between organizations in terms of their propensity to turn to the private sector – one of the classic recipes for achieving efficiency gains – for the delivery of administrative overhead, and helps practitioners gain insight into the determinants of administrative overhead outsourcing.